KEPEMIMPINAN KEPALA SEKOLAH: UPAYA MENINGKATKAN MUTU PENDIDIKAN MELALUI KONSEP MANAJEMEN BERBASIS SEKOLAH - Asep Priatna; Ina Marlina (Edum Journal, 2021)
Abstract, The Objective of study is to increase the quality of human resources of the principal as an element of leadership to administer the educational program of the public junior high schools.The problem of research is ‘How does the role of principle in the effeart to increase the educational quality through the concept of the school-based management ?. The Methtod of the research is descriptive method with qualitative approach with subjects of research are principal and teachers of the state junior high school in subdistrict of Subang. The findings of research can be formulated as in following: 1].The role of principal as a manager of education 2].The role of principal as an educator 3].The role of principal as an administration 4].The role principal as a supervisor 5]. The effors were done by principal in order to increase the quality of education, i,e. by [a],doing the establishment of the teacher profesionality, [b].activating the meeting of school subject matter teachers, [c].building the guided discussion group, and [d]. Acquisition of the school library textbooks.